Affetti e passioni nel pensiero medievale - Vecchio, Silvana (Studia Romanica Posnaniensia, 2018)
The article points out the stages of medieval reflection on affectivity. In controversy with stoical positions, Augustine re-evaluates passions, linking them to the Passion of Christ, and describes them as motions of will that may be both good and bad, depending on the object to which they are directed. This christianization of passions dominates high-medieval culture, intertwining with the most widespread moral system, that of the seven deadly sins. From the XII century and especially in the thirteenth century, the translation of the Greek and Arabic philosophical sources and a renewed interest in the study of the soul and its faculties, allow to develop new doctrines about passions, culminating in the treatise of Thomas Aquinas, the most complete and systematic analysis of the emotional universe up to the modern age.